The History of Don Quixote, Volume 1, Part 07 - Cervantes Saavedra, Miguel de, 1547-1616; Doré, Gustave, 1832-1883; Ormsby, John, 1829-1895 (Salt Lake City, UT : Project Gutenberg, 2004)
"The History of Don Quixote, Volume 1, Part 07" by Miguel de Cervantes Saavedra is part of a novel originally published in 1605. The story follows Alonso Quixano, a man driven mad by chivalric romances who reinvents himself as the knight-errant Don Quixote. Accompanied by his earthy squire Sancho Panza, he embarks on delusional adventures, mistaking windmills for giants and inns for castles. This founding work of Western literature explores the collision between fantasy and reality with both humor and depth. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Don_Quixote
Illustrated.
Release date is 2004-06-01
Produced by David Widger
Keywords: Spain -- Social life and customs -- 16th century -- Fiction; Knights and knighthood -- Spain -- Fiction; Picaresque literature; Romances